E-Government and public service delivery in Nigeria - Lawan, Bello Muhammed; Ajadi, Ishola Abdulrasaq; Kayode, Abdulkareem Abdulrazaq; Yaru, Abubakar Umar (Penerbit Universiti Kebangsaan Malaysia, 2020)
The innovation in ICTs and the resulting emergence of the internet were strong drivers for shifting to an information era from the industrial age. In this movement, nations found succour in using information technologies for service delivery and this becomes the most significant epoch in the history of governance transformation. Despite the huge commitment of the government towards the e-government project in Nigeria, significant growth is not yet recorded on the use of ICT in governance as evidenced in the 2018 recent ranking by the United Nations on e-Government global ranking and assessment, Nigeria was positioned on 143rd of the 193 United Nation Member States. This paper therefore sought to investigate the reasons for the poor performance in the sector. This was done through secondary data collected with a structured interview from ICT directors of eight (8) purposively selected Federal Agencies in Nigeria. With due use of thematic analysis of the interview data, the study found that the challenges confronting e-government implementation in Nigeria were national challenges such as infrastructural deficiency, ICT illiteracy in addition to peculiar challenges like data privacy, security concerns. The paper thus concluded that unless these problems are tacked, the likelihood of having a successful e-government implementation outing in Nigeria would remain a mirage.